1992
DOI: 10.1046/j.1469-0705.1992.02010051.x
|View full text |Cite
|
Sign up to set email alerts
|

In utero early suspicion of superfetation by ultrasound examination: a case report

Abstract: We report the case of a dichorionic and diamniotic pregnancy with the unique feature of an early ultrasound diagnosis of a 4-week size difference, which persisted throughout pregnancy. At birth, the twins had a 1-month difference in physical and neurological maturity. We believe that only the phenomenon of a superfetation can explain this difference. We report the cases found in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…Without evidence of multiple ovulations and their respective CLs as well as the use of early ultrasonography fetal size differences cannot always be attributed to SF (Rosenberg, 1954; Scrimgeour & Baker, 1974; Baijal et al , 2007). However, there is good evidence for SF in humans resulting from the use of artificial reproductive technologies (Bonnar, 1865; Walter, Hasenohr & Kerin, 1975; Soudre et al , 1992; Dmowsky, De Orio & Rana, 1997; Steck & Bussen, 1997). Harrison et al (2005) demonstrated discordance in development after the transfer of three embryos.…”
Section: Evidence For Superfetation In Mammalsmentioning
confidence: 99%
“…Without evidence of multiple ovulations and their respective CLs as well as the use of early ultrasonography fetal size differences cannot always be attributed to SF (Rosenberg, 1954; Scrimgeour & Baker, 1974; Baijal et al , 2007). However, there is good evidence for SF in humans resulting from the use of artificial reproductive technologies (Bonnar, 1865; Walter, Hasenohr & Kerin, 1975; Soudre et al , 1992; Dmowsky, De Orio & Rana, 1997; Steck & Bussen, 1997). Harrison et al (2005) demonstrated discordance in development after the transfer of three embryos.…”
Section: Evidence For Superfetation In Mammalsmentioning
confidence: 99%
“…The occurrence of ovulation, conception and embryo implantation in a patient that already carries an ongoing pregnancy (otherwise know as superfetation) is a quite rare phenomenon in human beings. It has been reported in a few cases in which ultrasound examination showed several weeks of discordance in size between two fetuses of a twin pregnancy (Baijal et al, 2007;Harrison et al, 2005;Pape et al, 2008;Soudre et al, 1992;Tuppen et al, 1999). In some reported cases, the alternative hypothesis of marked intrauterine growth restriction of one of the twins was ruled out by neurosonography and ophthalmological examination that confirmed gestational age assessment (Harrison et al, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…This is rare in humans with less than 10 cases of superfetation are described in the literature [4]. One of the early cases of superfetation was described in 1992 showing dichorionic diamniotic twins with a 4-week size and consistent growth difference shown through ultrasound measurements [5]. In this same case study at birth Twin 1 was 37 weeks and Twin 2 was 33-34 weeks [5].…”
mentioning
confidence: 76%